Factors affecting Kager’s fat pad stiffness and its normal reference value in healthy adults using 2-dimensional shear wave elastography - Abdalmalek Ismail Aburabee; Sook Sam Leong; Mohd Shukry Khalid; Shafini Mohamad (Journal of Clinical and Health Sciences, 2026)
Introduction: Acute ankle sprains account for 15-20% of sports-related injuries among athletes, with prolonged instability leading to gait issues, altered ankle posture, and Achilles tendon mechanics, while the adjacent Kager’s fat pad (KFP) is prone to inflammation from trauma, infection, or tumors. To determine factors that affect the stiffness of KFP and establish the median stiffness in healthy individuals using two-dimensional shear wave elastography (2D SWE). Methods: A total of sixty-one healthy volunteers were scanned using SWE to measure the right KFP. A single-layer gel was applied between the transducer and the posterior aspect of the ankle skin surface with the subjects in prone position and extending their ankles. Longitudinal plane was obtained to visualize the anatomical structures of the ankle joint, with a specific focus on the right KFP. A 1 mm region of interest (ROI) was positioned within the KFP. No pressure was applied during SWE image acquisition to avoid image artifact. Results: The Chi-square test revealed no significant associations between gender and stiffness. Spearman’s rho test revealed no significance difference between BMI, age, and KFP stiffness, but physical activity correlated significantly with stiffness (ρ(59) = 0.773, p